2017
DOI: 10.1007/s00018-017-2701-z
|View full text |Cite
|
Sign up to set email alerts
|

Master regulatory role of p63 in epidermal development and disease

Abstract: The transcription factor p63 is a master regulator of epidermal development. Mutations in p63 give rise to human developmental diseases that often manifest epidermal defects. In this review, we summarize major p63 isoforms identified so far and p63 mutation-associated human diseases that show epidermal defects. We discuss key roles of p63 in epidermal keratinocyte proliferation and differentiation, emphasizing its master regulatory control of the gene expression pattern and epigenetic landscape that define epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
151
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(159 citation statements)
references
References 98 publications
8
151
0
Order By: Relevance
“…We previously showed that TP63 controls the expression of high-molecular weight keratins (KRT5, KRT6, and KRT14) and suppresses EMT (Choi et al, 2014b; Tran et al, 2013). The central role of p63 in the maintenance of epithelial phenotype and EMT was confirmed in several variants of solid tumors (Soares and Zhou, 2018; Stacy et al, 2017; Tanaka et al, 2018). We therefore performed additional analyses to further characterize the role of EMT in SARC.…”
Section: Resultsmentioning
confidence: 88%
“…We previously showed that TP63 controls the expression of high-molecular weight keratins (KRT5, KRT6, and KRT14) and suppresses EMT (Choi et al, 2014b; Tran et al, 2013). The central role of p63 in the maintenance of epithelial phenotype and EMT was confirmed in several variants of solid tumors (Soares and Zhou, 2018; Stacy et al, 2017; Tanaka et al, 2018). We therefore performed additional analyses to further characterize the role of EMT in SARC.…”
Section: Resultsmentioning
confidence: 88%
“…The skin, the largest organ in the body, is highly organized and endowed with a remarkable repair and turnover potential to serve as the first line defense of the internal milieu, among a multitude of other physiological roles. P63 is a master regulator of skin development, and its deficiency is known to result in severely anomalous development of skin and other ectoderm‐derived structures . Several downstream effectors of P63 have similarly been implicated in various skin disorders in human, for example, KDF1 .…”
Section: Introductionmentioning
confidence: 99%
“…P63 is a master regulator of skin development, and its deficiency is known to result in severely anomalous development of skin and other ectoderm-derived structures. 1 Several downstream effectors of P63 have similarly been implicated in various skin disorders in human, for example, KDF1. 2 Recently, dominant mutations in one such effector, PERP, have been detected in patients with keratoderma, a phenotype characterized by excessive scaling of skin.…”
mentioning
confidence: 99%
“…). Mutations in the TP63 gene have been associated with human developmental diseases and skin abnormalities (Li & Xiao , Soares & Zhou ), as well as with different cancer types, such as lung, breast, bladder and squamous cell carcinoma (Hu et al . , Zhang et al .…”
Section: Introductionmentioning
confidence: 99%